Valepotriates From the Roots and Rhizomes of Valeriana jatamansi Jones as Novel N-Type Calcium Channel Antagonists - Dong, Fa-Wu; Jiang, He-Hai; Yang, Liu; Gong, Ye; Zi, Cheng-Ting; Yang, Dan; Ye, Chen-Jun; Li, Huan; Yang, Jian; Nian, Yin; Zhou, Jun; Hu, Jiang-Miao (Frontiers in Pharmacology, 2018)
The roots and rhizomes of V. jatamansi have long been used as folk medicine in Asia and usually named as ″Zhizhuxiang″ in Chinese for the treatment of abdominal distention and pain. However, its active ingredients and molecular targets for treatment of abdominal pain remain unrevealed. Inhibitors of Cav2.2 N-type voltage-gated calcium channels (VGCCs) are actively sought after for their potential in treating pain, especially chronic pain. As far as we know, the method used for seeking analgesic active ingredient from plant material has rarely been reported. The analgesic potentials of the EtOH extract (0.01 mg/ml) of the roots and rhizomes of V. jatamansi and its EtOAc, n-BuOH and H2O soluble parts (0.01 mg/ml, respectively) were tested herein on Cav2.2, using whole-oocyte recordings in vitro by tow-electrode voltage clamp. The results indicated that the EtOAc-soluble part exhibiting the most potent inhibition of Cav2.2 peak current (20 mv). The EtOAc-soluble part was then subjected to silica gel column chromatography (CC) and giving 9 fractions. Phytochemical studies were carried out by repeated CC and extensive spectroscopic analysis after the fraction was identified active and got seventeen compounds (1-17). All isolates were then sent further for bioactive verification (1 and 3 at concentration of 10 μM, others at 30 μM). In addition, the selectivity of compounds 1 and 3 were tested on various ion channels including Cav1.2, Cav2.1 and Cav3.1 VGCCs and Kv1.2, Kv2.1, Kv3.1 and BK potassium channels. The results indicated that compounds 1 and 3 (an abundant compound) inhibited Cav2.2 with an EC50 of 3.3 μM and 4.8 μM respectively and had weaker or no effect on Cav1.2, Cav2.1 and Cav3.1 VGCCs and Kv1.2, Kv2.1, Kv3.1 and BK potassium channels. Compounds 1 and 3 appear to act as allosteric modulators rather than pore blockers of Cav2.2, which may play crucial role in attenuating nociception. The results of present research indicated that the ethnopharmacological utilization of V. jatamansi for relieving the abdominal distention and pain may mediate through Cav2.2 channel. Our work is the first demonstration of inhibition of Cav2.2 by iridoids, which may provide a fresh source for finding new analgesics.